Self-Reported Population Health: An International Perspective based on EQ-5D - Szende, Agota; Janssen, Bas; Cabases, Juan (Springer Nature, 2014)
Biomedicine general; Public Health; Quality of Life Research; Population Health; EQ-5D; Quality-of-Life; Utilities